Que sonidos hay? - Jimenez, Vita. (Bloomington, Minn. : Yellow Umbrella Books, 2006)
"Simple text and photos present loud and soft sounds"--Provided by publisher.
Includes index.
Keywords: Sound -- Juvenile literature; Spanish Juvenile Beginning Readers